Role of WNT10A in failure of tooth development in humans and zebrafish. Issue 6 (14th September 2017) - Yuan, Qiuping; Zhao, Min; Tandon, Bhavna; Maili, Lorena; Liu, Xiaoming; Zhang, Anqi; Baugh, Evan H.; Tran, Tam; Silva, Renato M.; Hecht, Jacqueline T.; Swindell, Eric C.; Wagner, Daniel S.; et al.
Abstract: Background: Oligodontia is a severe form of tooth agenesis characterized by the absence of six or more permanent teeth. Oligodontia has complex etiology and variations in numerous genes have been suggested as causal for the condition. Methods: We applied whole‐exome sequencing (WES) to identify the cause of oligodontia in a 9‐year‐old girl missing 11 permanent teeth. Protein modeling and functional analysis in zebrafish were also performed to understand the impact of identified variants on the phenotype. Results: We identified a novel compound heterozygous missense mutation in WNT10A (c.637G>A:p.Gly213Ser and c.1070C>T:p.Thr357Ile) as the likely cause of autosomal recessive oligodontia in the child. Affected residues are located in conserved regions and variants are predicted to be highly deleterious for potentially destabilizing the protein fold and inhibiting normal protein function. Functional studies in zebrafish embryos showed that wnt10a is expressed in the craniofacies at critical time points for tooth development, and that perturbations of wnt10a expression impaired normal tooth development and arrested tooth development at 5 days postfertilization (dpf). Furthermore, mRNA expression levels of additional tooth development genes were directly correlated with wnt10a expression; expression of msx1, dlx2b, eda, and axin2 was decreased upon wnt10a knockdown, and increased upon wnt10a overexpression. Conclusions: Our results reveal a novel compound heterozygous variant in WNT10A as pathogenic for oligodontia, and demonstrate that perturbations of wnt10a expression in zebrafish may directly and/or indirectly affect tooth development recapitulating the agenesis phenotype observed in humans. Abstract : Our results reveal a novel compound heterozygous variant in WNT10A as pathogenic for oligodontia, and demonstrate that perturbations of wnt10a expression in zebrafish may directly and/or indirectly affect tooth development recapitulating the agenesis phenotype observed in humans.